2009
DOI: 10.1592/phco.29.4.365
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Intermittent Hypoxia on Myocardial and Hepatic P‐glycoprotein Expression in a Rodent Model

Abstract: Study Objective-The purpose of this study was to determine if intermittent hypoxia that mimics obstructive sleep apnea would upregulate myocardial and hepatic p-glycoprotein protein and Abcb1a/ Abcb1b mRNA expression.Design-Prospective, randomized, blinded, parallel designed animal study Setting-University Research LaboratoryParticipants-Thirty adult, male Sprague-Dawley rats Intervention-We assigned rats to either two weeks of intermittent hypoxia similar to sleep apnea (N=12) or control treatment (N=18) (no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
0
9
0
2
Order By: Relevance
“…Dopp et al demonstrated an increase in Abcb1a mRNA ( Abcb1 is the gene that codes for p-glycoprotein) expression in the heart and liver of mice exposed to 2 wks of cyclical intermittent hypoxia. 119 Gong et al showed cerebral ischemic preconditioning with intermittent hypobaric hypoxia increases glutamate transporter 1 in neurons of the hippocampus of rats. 120 But expression of other transporters is decreased.…”
Section: Effects Of Intermittent Hypoxia On Bbb Microvessel Permeabilmentioning
confidence: 99%
“…Dopp et al demonstrated an increase in Abcb1a mRNA ( Abcb1 is the gene that codes for p-glycoprotein) expression in the heart and liver of mice exposed to 2 wks of cyclical intermittent hypoxia. 119 Gong et al showed cerebral ischemic preconditioning with intermittent hypobaric hypoxia increases glutamate transporter 1 in neurons of the hippocampus of rats. 120 But expression of other transporters is decreased.…”
Section: Effects Of Intermittent Hypoxia On Bbb Microvessel Permeabilmentioning
confidence: 99%
“…В эксперименте на 30 половозрелых крысах (две группы из 12 опытных и 18 контрольных животных) с использованием методов Western blotting и ПЦР показано повышение экспрессии Pgp в миокарде, а также увеличение количества миокардиальной и печеночной иРНК гена mdr1a и миокардиальной иРНК гена mdr1b в результате воздействия на жи-вотных интермиттирующей дыхательной гипоксии в течение двух недель [14].…”
Section: Aadsorasunclassified
“…Данная область представляет собой последовательность нуклеотидов 5'-GCGTG-3', расположенную на рас-стоянии от -49 до -45 пар нуклеотидов от сайта старта транскрипции [12,14].…”
Section: Aadsorasunclassified
“…So the expression of MDR1 under hypoxia at high altitude will make a major contribution to absorption, distribution, metabolism, excretion of its substrates. Many previous studies have introduced the changes of the mRNA and protein expression of MDR1 in different tissues under hypoxia (see Table 2; Bush & Li, 2002;Comerford et al, 2002;Ding et al, 2010;Dopp et al, 2009;Fradette et al, 2007;Ho et al, 2003;Lazarowski et al, 2007;Lotz et al, 2007;Maillefert et al, 1996;Marie et al, 1991;Musto et al, 1991;Pirker et al, 1991;Schaich et al, 2005;Wartenberg et al, 2003;Xia et al, 2004;Yamada et al, 2000). But most of the experimental samples are tumor tissues or tumor cells that are pathological anoxia; what we should do in future is to do the research by use normal tissues or cells under hypoxia conditions.…”
Section: Substrate Specificity Of Mdr1mentioning
confidence: 99%